137k views
1 vote
I'm having trouble solving this simultaneous equation4a – 5b = 52a – 3b = 2

User Eegloo
by
4.9k points

1 Answer

2 votes

Given:


\begin{gathered} 4a-5b=5\ldots\ldots\ldots(1) \\ 2a-3b=2\ldots\ldots\ldots(2) \end{gathered}

To solve for a and b:

Multiply equation (2) by 2 we get,


4a-6b=4\ldots\ldots\ldots(3)

Subtract equation (3) from (1) we get,


b=1

Substitute b=1 in equation (2) we get,


\begin{gathered} 2a-3(1)=2 \\ 2a=2+3 \\ 2a=5 \\ a=(5)/(2) \end{gathered}

Hence, the value of a and b are,


\begin{gathered} a=(5)/(2) \\ b=1 \end{gathered}

User Gaj Julije
by
5.6k points